Вплив форми латерально-впорядкованих наноструктур на ефективність поверхнево-підсиленого раманівського розсіювання - Indutnyi, I.Z.; Yukhymchuk, V.O.; Mynko, V.I.; Mamykin, S.V.; Mazur, N.V.; Isaieva, O.F.; Dzhagan, V.M.; Danko, V.A.; Yefanov, V.S.; Korchovyy, A.A.; Lytvyn, P.M. (Publishing house "Academperiodika", 2024)
Bigratings of two types, with laterally arranged domes or holes, are formed on relief-forming chalcogenide layers As10Ge30S60 using the interference photolithography method. Coating such bigratings with aluminum (80 nm), silver (70 nm), and gold (10 nm) layers makes it possible to obtain surface-enhanced Raman scattering (SERS) substrates of two types. Changes in the surface morphology of SERS substrates during the process of their formation are studied using the atomic force microscopy. It is shown that the periods of SERS substrates of both types are about 1200 nm, and the holes’ depth and the domes’ height are about 350 nm. The subsequent deposition of metal layers on the formed reliefs had little effect on the holes’ diameters and the domes’ dimensions. The measurements of the spectral-angular dependences of the polarized light reflection from the formed SERS substrates in a wavelength interval of 0.4–1.1 μm and at incidence angles of 10–70∘ demonstrated the excitation of both local plasmon resonances (in the structures with domes) and plasmon-polariton surface waves (in the structures of both types) in those substrates. It is shown that the formed structures with laterally ordered domes and holes are effective SERS substrates. It is found that the structures with domes used to excite the Raman spectra of the laser radiation with wavelengths of 457, 532, and 671 nm are an order of magnitude more effective when enhancing the Raman signal from the standard R6G analyte. It occurs, because, when the exciting laser radiation is normally incident on the structures with domes, localized plasmons are effectively excited in spectral intervals with maxima at 488 and 676 nm, whereas such features were not observed in the absorption spectra of the structures with holes.